Konsep Sehat-Sakit : Sebuah Kajian Filsafat - Putu Emy Suryanti (Sanjiwani: Jurnal Filsafat, 2021)
Nowadays, science and technology have developed very rapidly. The development of science and technology has brought many conveniences for humans, so that it can help overcome various problems in life. However, on the other hand, there is a great deal of concern over the increasingly rapid development of science and technology because no person or institution has the authority to prevent the negative impact of the development of science and technology. Meanwhile, science and technology are increasingly losing their fundamental spirit, which makes human beings increasingly enslaved by science and technology. This causes advances in science and technology to be supported by philosophical studies. Likewise with health science, philosophical studies both in the ontology, epistemology and axiology are needed. One of the fundamental things in health is the concept of health-sickness. The study of the concept of health-sickness from a philosophical perspective is expected to have a positive impact along with the development of health science so that it can increase individual and community understanding of holistic health with the long-term hope of being able to improve public health status and support the Government in health development programs.